Congenital cytomegalovirus retinitis of prematurity: a case report and literature review - Yihui Li; Wenqiang Sun; Xinyun Jin; Lei Zhao; Xueping Zhu (Frontiers in Pediatrics)
IntroductionOphthalmopathy induced by cytomegalovirus (CMV) infection is most common in immunodeficient patients without other congenital infections. This paper reports a clinical case of retinitis due to congenital CMV infection in a preterm infant and reviews the relevant literature.Case presentationA 2-day-old female infant at 36+2 gestation weeks presented with a 2-day history of scattered bleeding spots across the body, hemorrhagic diathesis, thrombocytopenia, positive blood CMV IgM, and blood and urine CMV DNA levels significantly above the detection limit by PCR analysis. Maternal serological examination indicated blood CMV IgM positivity. The laboratory test results, CMV IgM positivity in the mother's blood was used to confirm a diagnosis of congenital CMV infection. Later, antiviral treatment with ganciclovir was provided for 3 weeks. Fundus examination indicated a few white exudates along the peripheral retina in both eyes, with a white sheath of peripheral retinal vessels above the temporal plane in the right eye. A diagnosis of CMV retinitis was considered after obtaining abnormal fluorescein fundus angiography results. Ganciclovir was administered at 0.5 mg weekly into the vitreous cavities of the eyes for 3 weeks, and the vascular white sheaths disappeared. Retinitis recurred at 6 months of age, and antiviral treatment was recommended. However, the family rejected it.ConclusionCongenital cytomegalovirus retinitis carries substantial risks. For infants suspected of this condition, early initiation of antiviral therapy is crucial to enable timely intervention, improve prognosis, and enhance the child's quality of life.